Presence of rnicroorganisms in young leaves, inflorescences and seeds of african oil palm (Elaeis guineensis Jacq) - Cid, Luis Pedro Barrueto (Pesquisa Agropecuaria Brasileira, 2014)
Segments of different parts of African oil palm trees were observed through light microscopy. Results showed the presence of microorganisms of various size, but with no aspect of Phytomonas. Structures that look like coccus or bacilli, but in less density, were also observed.